Hepatic Radiofrequency Ablation: Monitoring of Ablation-Induced Macrophage Recruitment in the Periablational Rim Using SPION-Enhanced Macrophage-Specific Magnetic Resonance Imaging. Issue 9 (6th September 2021) - Collettini, Federico; Brangsch, Julia; Reimann, Carolin; Chapiro, Julius; Savic, Lynn Jeanette; Buchholz, Rebecca; Keller, Sarah; Hamm, Bernd; Goldberg, S. Nahum; Makowski, Marcus R.
Abstract : Objectives: Macrophages accumulating in the periablational rim play a pivotal role in initiating and sustaining the perifocal inflammatory reaction, which has been shown to be at least 1 of the mechanisms responsible for the systemic pro-oncogenic effects of focal hepatic radiofrequency ablation (RFA). Herein, we tested the hypothesis to use superparamagnetic iron oxide nanoparticle (SPION)–enhanced magnetic resonance imaging (MRI) for noninvasive quantification of iron-loaded macrophages in the periablational rim of VX2 tumor-bearing rabbits. Materials and Methods: Twelve VX2 tumor-bearing rabbits underwent MRI immediately after and up to 3 weeks after focal hepatic RFA. For noninvasive quantification of macrophage accumulation in the periablational rim, animals were scanned before and 24 hours after SPION injection. T2*-weighted images were analyzed and correlated with histopathological and immunohistochemical findings. Furthermore, correlations with quantitative measurements (ICP-MS [inductively coupled plasma–mass spectrometry] and LA-ICP-MS [laser ablation–ICP-MS]) were performed. Results: SPION-enhanced T2*-weighted MRI scans displayed a progressive increase in the areas of signal intensity (SI) loss within the periablational rim peaking 3 weeks after RFA. Accordingly, quantitative analysis of SI changes demonstrated a significant decline in the relative SI ratio reflecting a growing accumulation of iron-loaded macrophages in the rim. Histological analyses confirmed a progressive accumulation of iron-loaded macrophages in the periablational rim. The ICP-MS and LA-ICP-MS confirmed a progressive increase of iron concentration in the periablational rim. Conclusions: SPION-enhanced MRI enables noninvasive monitoring and quantification of ablation-induced macrophage recruitment in the periablational rim. Given the close interplay between ablation-induced perifocal inflammation and potential unwanted tumorigenic effects of RFA, SPION-enhanced MRI may serve as a valuable tool to guide and modulate adjuvant therapies after hepatic RFA.